2011
DOI: 10.1161/strokeaha.111.623405
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Extravasation on Computed Tomography Angiography Predicts Clinical Outcome in Primary Intracerebral Hemorrhage

Abstract: Background and Purpose-Several retrospective studies suggested that contrast extravasation on CT angiography predicts hematoma expansion, poor outcome, and mortality in primary intracerebral hemorrhage. We aimed to determine the predictive value of contrast extravasation on multidetector CT angiography for clinical outcome in a prospective study. Methods-In 160 consecutive patients with spontaneous intracerebral hemorrhage admitted within 6 hours of symptom onset, noncontrast CT and multidetector CT angiograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
70
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 22 publications
6
70
2
2
Order By: Relevance
“…Akin to prior nontraumatic ICH studies [12][13][14][15][16][17][18][20][21][22]38 and a smaller cerebral contusion study, 25 our results demonstrate the prognostic value of contrast extravasation in traumatic intracrananial injuries. Similarly, earlier MR imaging series evaluated "enhancement" of traumatic intra-and extra-axial hematomas, also suggesting a predictive value of extravasation in this setting but were limited by significantly smaller sample sizes.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Akin to prior nontraumatic ICH studies [12][13][14][15][16][17][18][20][21][22]38 and a smaller cerebral contusion study, 25 our results demonstrate the prognostic value of contrast extravasation in traumatic intracrananial injuries. Similarly, earlier MR imaging series evaluated "enhancement" of traumatic intra-and extra-axial hematomas, also suggesting a predictive value of extravasation in this setting but were limited by significantly smaller sample sizes.…”
Section: Discussionsupporting
confidence: 66%
“…11 In nontraumatic ICHs, contrast extravasation on CTA has been shown to predict hematoma expansion, poor outcome, and mortality. [12][13][14][15][16][17][18][19][20][21][22][23] Despite CT reports dating back Ͼ30 years identifying contrast extravasation in traumatic head injuries, 24 there has been limited analysis of this sign in the setting of trauma. A recent study evaluated 22 patients with traumatic cerebral contusions and concluded that early parenchymal CE is associated with clinical progression, cerebral edema, clinical deterioration, and the need for subsequent surgery.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This could in part explain the high variability in positive predictive values reported in spot sign literature (24% to 79%). 2,3,5,6 In this study, we noted that active extravasation gives rise to large irregular patterns of intrahematoma contrast that mimic the appearance of multiple spot signs when viewed in the axial plane (Figure 2; online-only Data Supplement III). The presence of multiple spot signs is a robust predictor of HE 13,14 ; the positive predictive value for significant expansion increases from 61% for 1 spot sign to 100% for ≥4 spot signs.…”
Section: 12mentioning
confidence: 58%
“…1 Several reports proposed the CT angiography spot sign as a radiological marker predictive of HE in the acute setting. [2][3][4][5][6] Although the general assumption is that spot sign is the radiological correlate of active bleeding at the site of vessel rupture, its exact pathology is not known. A modest positive predictive value of 61% to predict HE 6 suggests that spot sign may be present even when bleeding has ceased, perhaps representing a site of arrested hemorrhage or associated microvascular lesion such as a microaneurysm.…”
mentioning
confidence: 99%